Customer Service / A Practical Approach Fifth Edition - Harris Elaine K (Prentice Hall, 2010)
This textbook develops the skills and strategies needed to build and maintain customer service excellence. What is Customer Service, The Challenges of Customer Service, Problem Solving, Strategy for Formulating a Plan for Success, Empowerment, Communications in Customer Service, Coping with Challenging Customers, Motivation, Leadership in Customer Service, Customer Retention and Measurement of Satisfaction, Technology and Customer Service, Excellence in Customer Service.